FIRST AND SECOND ORDERS OF SUTURE COMPLEXITY IN AMMONITES: A NEW METHODOLOGICAL APPROACH USING FRACTAL ANALYSIS - Perez-Claros Ju.A.; Palmqvist P.; Oloriz F. (My University, 2002)
The study of septal patterns in ammonoids has been centered on functional and/or constructional issues. Complexly fluted septa have been considered as complementary structures that reinforce the ammonite shell, their frilled sutures possibly manifesting the demand for strength. Ammonitic sutures display features that denote typical fractal behavior, since they can present very long perimeters relative to the contiguous shell areas, and most provide evidence of statistical self-similarity when observed at varying scales of magnification. However, there is a lower limit of scale measurements below which the fractal behavior of the curve no longer holds, and the perimeter length/step size relationship approaches an Euclidean geometry. This paper describes a new methodology that allows the accurate characterization of suture complexity in ammonoids using the technique of fractal analysis (step-line procedure). The proposed methodology helps to fix the position of this "cut-off point," allowing for independent estimates of the fractal dimensions of the curve for both large and small measurement scales (i.e., first and second orders of suture complexity). This approach improves the resolution of fractals in the analysis of suture complexity, thus facilitating the potential interpretation of suture patterns in functional/constructional, evolutionary and paleoecological terms.
Keywords: JURASSIC; AMMONOIDS; MORPHOMETRY; Mesozoic::Jurassic; Мезозой::Юрская